The interictal transcriptomic map of migraine without aura - Peter Petschner; Sahel Kumar; Duc A. Nguyen; Dora Torok; Zsofia Gal; Daniel Baksa; Kinga Gecse; Gyongyi Kokonyei; Hiroshi Mamitsuka; Gabriella Juhasz (The Journal of Headache and Pain)
Abstract Background The present study aimed to deliver a replicable transcriptomic map of migraine without aura (MO) and its comprehensive, genome- and drug discovery focused analysis to identify hypotheses for future research- and clinical attempts. Methods We recruited 30 controls and 22 MO patients without serious chronic comorbidities/regular medication intake. RNA-sequencing was conducted interictally at two different time points to identify replicable differential gene expression and enriched pathways. Subsequent refining and functional analyses were performed, including: 1) testing additional patient factors, 2) running genetic association analysis on migraine in the UK Biobank (UKB) and our cohort, and 3) predicting drug binding with AutoDock Vina and machine learning to proteins of transcriptomic changes. Results Difference in CYP26B1 was identified as key alteration in migraine. Gene set enrichment analysis identified 88 replicated, significant, exclusively downregulated core pathways, including metabolic, cardiovascular, and immune system-related gene sets and 69 leading genes, like CORIN. Logistic regression of leading genes’ and vitamin A pathway-related polymorphisms identified 11 significant polymorphisms in LRP1. Confirmatory analyses excluded a substantial impact of sex, allergy and different vitamin A/retinol intake. Binding simulations and predictions pointed to potential future drug molecules, like tetrandrine and probucol. Conclusion The replicable transcriptomic map of MO and functional analyses: 1) identified pathomechanisms related to metabolic, cardiovascular and immune system related processes on a molecular level, 2) reported gene level hits, 3) proposed novel potential etiology, like LRP1-induced decreased retinoic acid signaling, and 4) delivered novel drug candidates for the disorder.